2022
DOI: 10.1186/s13020-022-00676-7
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics combined with transcriptomic and mass spectrometry imaging analysis of the Asiatic toad (Bufo gargarizans) during metamorphosis and bufadienolide accumulation

Abstract: Background To adapt to life on land, Asiatic toads (Bufo gargarizans) must remodel their bodies and refine their chemical defenses in water. The full scope of the mechanisms underlying these processes has yet to be revealed. Bufadienolides (BDs) are chemical defense substances secreted by toads when they are in danger, and they have high medicinal value in treating heart failure, cancer, and hepatitis. However, the artificial breeding of toads to increase BDs has been unsuccessful due to the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…The metabolite profiles were studied in detail by metabolomics to explore the mechanisms of thymus-derived T cell-mediated ADRs after injecting SMI ( 44 ). The current study found SMI significantly altered the metabolic profile of BALB/c mice and BALB/c nude mice in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The metabolite profiles were studied in detail by metabolomics to explore the mechanisms of thymus-derived T cell-mediated ADRs after injecting SMI ( 44 ). The current study found SMI significantly altered the metabolic profile of BALB/c mice and BALB/c nude mice in vivo .…”
Section: Discussionmentioning
confidence: 99%